Antibiotic practices in non-condylar mandibular fractures: a Maxillofacial Trainee Research Collaborative (MTReC) UK-wide survey. Issue 3 (April 2022) - Kumar, D.; Dawoud, B.E.S.; Kent, S.; MTReC,; Kyzas, P.
Abstract: Non-condylar mandibular fractures are consdered 'open' fractures and as such are thought to require prophylactic antibiotics. There is no overall consensus on the optimal regimen or choice of antibiotic in the preoperative and postoperative periods due to a lack of high-quality evidence. We therefore set out to ascertain the current UK-wide practice of antibiotic prescribing for non-condylar mandibular fractures. We used a web-based online survey (Google Forms) that was disseminated via email and social media platforms to oral and maxillofacial surgery (OMFS) consultants and trainees of all grades. The questions focused on usual antibiotic practices and typical clinical management of non-condylar mandibular fractures. We gathered information on preoperative antibiotics, and on perioperative and postoperative periods. We collected data from 50 different UK OMFS units representing a broad snapshot of national practice. The majority of responders were speciality trainees (36%) followed by dental core trainees (34%). A total of 45/50 centres routinely admitted patients, and preoperative intravenous antibiotics were commenced on admission by 77/89 respondents, intravenous being the chosen route in all cases. In the preoperative period 81% prescribe co-amoxiclav. In 91% of cases, open reduction and internal fixation (ORIF) was on general emergency (CEPOD) operating lists, whilst dedicated OMFS trauma lists accounted for 9%. With respect to timing, 49% aimed to carry out ORIF within 24 hours from the time of admission, 44% aimed for surgery within 24 - 48 hours, and 6% aimed for surgery on a semielective basis (48 hours or more). Postoperative antibiotics were prescribed routinely by 88% of responders. Preoperative intravenous prophylactic antibiotics are commonplace in non-condylar mandibular fractures. This UK-wide survey demonstrated significant variability in antibiotic prescribing practices, especially in the postoperative period. Most units still rely on CEPOD emergency theatres to provide the capacity for ORIF in this patient group.